The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s00280-010-1287-z
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor valproic acid sensitizes human and canine osteosarcoma to doxorubicin

Abstract: Purpose-Osteosarcoma (OS) remains an incurable and ultimately fatal disease in many patients, and novel forms of therapy are needed. Improved models of OS that more closely mimic human disease would provide more robust information regarding the utility of novel therapies. Spontaneous OS in dogs may provide such a model. Pharmacologic inhibition of histone deacetylase (HDAC) enzymes has a variety of anti-tumor effects but may demonstrate the most utility when utilized in combination with standard cytotoxic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…The antitumor effect of VPA by induction of cell apoptosis has been reported in various cancers, such as small cell lung cancer, chronic lymphocytic leukemia, and hepatoma [17,34,35]. VPA treatment also sensitizes tumor cells to some first-line antitumor drugs, such as doxorubicin, cisplatin, and etoposide [16,17]. Consistent with these reports, our results demonstrated that a combination of CuB with VPA overcame the resistant compensatory response and multiploidization effect induced by CuB.…”
Section: Discussionsupporting
confidence: 81%
“…The antitumor effect of VPA by induction of cell apoptosis has been reported in various cancers, such as small cell lung cancer, chronic lymphocytic leukemia, and hepatoma [17,34,35]. VPA treatment also sensitizes tumor cells to some first-line antitumor drugs, such as doxorubicin, cisplatin, and etoposide [16,17]. Consistent with these reports, our results demonstrated that a combination of CuB with VPA overcame the resistant compensatory response and multiploidization effect induced by CuB.…”
Section: Discussionsupporting
confidence: 81%
“…The effects of H3 acetylation on transcription of a host of prosurvival and transforming genes makes co-therapy using HDAC inhibitors a promising co-therapy in treatment of drug-refractory tumors to circumvent activation of survival pathways [22,34,35]. Our results demonstrate that therapeutic levels of VPA in an in vitro prostate cancer system had greatly increased the histone H3 acetylation in DU145 cells.…”
Section: Discussionmentioning
confidence: 78%
“…Inhibition of histone deacetylases is one of the effects of VPA on cells (54,57), which has been proposed to have an antiviral effect on latent infections (11,29,31,61). To address the implication of this mechanism on the inhibition observed in this study, the effect of TSA-another HDAC inhibitor (8)-on the infection of FMDV, SFV, SINV, VSV, VACV, LCMV, ASFV, WNV, and USUV was tested.…”
Section: Effect Of Vpa On Viral Infectionmentioning
confidence: 99%
“…The proposed cellular targets of VPA are diverse, including (i) interruption of ␄-amino butyric acid (GABA) signaling, (ii) inhibition of histone deacetylases (HDAC), (iii) modulation of sodium channel activity, (iv) inhibition of glycogen synthase kinase 3, and (v) disruption of membrane lipid metabolism, including that of phosphatidylinositol (48,53,54,57,59).…”
mentioning
confidence: 99%